Impact of dietary protein hydrolysates on skeleton quality and proteome in Diplodus sargus larvae - Vareilles, Mahaut (2014)
In order to investigate the effects of dietary protein hydrolysates (PH) on larval growth performance, skeleton quality and proteome expression, triplicate groups of white seabream (Diplodus sargus) larvae were co-fed from first-feeding with live feed and three microencapsulated diets differing in the molecular weight of their PH fraction (Control – inclusion of CPSP-90; H – inclusion of a high amount in 0.5–30 kDa hydrolysates; L – inclusion of a high amount in <0.5 kDa hydrolysates). At 15 days after hatching (DAH), proteome expression changes were assessed in entire larvae by twodimensional gel electrophoresis and the quality of larval skeleton was analysed at 28 DAH through double staining of cartilage and bone. Dietary PH fractions tested affected growth, the larvae fed diet L being significantly larger than those fed diet H, but it did not affect the incidence of deformed larvae, nor the number of deformities per fish. Two-dimensional analysis of larvae proteome allowed the detection and the comparative quantification of a total of 709 protein spots having a pI between 4 and 7, around half of which had an expression significantly affected by dietary treatment, the main difference being between proteome of Control larvae with those of both groups L and H. From these spots, 52 proteins involved in diverse processes such as cytoskeletal dynamics, energetic, lipoprotein, amino acid (AA), and nucleotide metabolisms, protein chaperoning and degradation, and signal transduction, were identified. This study revealed that the molecular weight of the dietary protein hydrolysate fraction had a minor impact on skeletal deformities in white seabream larvae, but affected growth performance and had a strong impact on larvae whole body proteome.